جۆرەكانی واتا لە سەردێڕدا لە روانگەی دركپێكردنەوە - ئەحمەد, پ.ی.د. تریفە عومەر (Sulaimani Journal for Humanities, 2023)
According to the cognitive perspective, the meaning of words is based on potential meaning and how meaning is accessed. This research, Cognition of Types of Word Meaning in Headlines, illustrates types of knowledge (Linguistic and Encyclopedic) that produce word concepts related to potential meaning. Based on these types of knowledge, Leach’s classification which categorizes word meaning into seven types is reduced into two main categories which are denotative meaning and connotative meaning. The former includes linguistic knowledge, and the latter includes the other types which are effective, social, reflective, collocation, and thematic meaning and they fall under the encyclopedic knowledge category. In the Kurdish media, headline composition is the most crucial component of the news through which a message is delivered. The journalist’s skill in experiencing and using lexicons has the main role in news editing. This skill, in addition to linguistic knowledge developed on encyclopedic knowledge, is based on each of experiential, expertise, and claimed knowledge. The main question of this research is concerned with the journalists’ skill in language usage, for this purpose, the types of meanings used by the journalists are made the criteria. Fourteen headlines from official websites such as Kurdsat News, Rudaw, NRT, Hawlati, Awena, Wsha, and Bas News are studied and justified according to the cognitive perspective. The analysis has led to two main conclusions. First, the types of knowledge are the basis for the reduction of Leach’s classification into two main categories. Secondly, lexical meaning, in relation to media semiotics, has more meaning than what is included in the denotative meaning based on the experience and skill of the journalist. Thus, the usage of the least types of meaning in the headlines hypothesizes the limited encyclopedic and experiential knowledge of the journalists.
Keywords: واتا كۆزانینی ئینسیكلۆپیدیایی كۆزانینی ئەزمونی كۆزانینی كارامەیی كرۆكەواتا توێكڵەواتا